Analysis of Bottled Water Brand Market Share Using the Markov Chain Method in the Faculty of Mathematics and Natural Sciences, Udayana University - Silvia Helena Ngantung; Ni Luh Putu Marina Atlanticia; Ni Made Jenni Prabayanti (International Journal of Applied Mathematics and Computing, 2026)
This study analyzes bottled water consumer traits and the market share of various brands over five years at the University of Udayana using the Markov chain method. Primary data from questionnaires show most consumers are female informatics students in dorms, consuming over 2 liters daily, mostly purchasing from stores. Decisions consider quality and brand, influenced by TV ads over peer recommendations. Market share in period 1: Aqua led with 52%, followed by Le Minerale (28%), Club (13%), Cleo (7%), and others (0%). In period 2, Aqua maintained 52%, Le Minerale rose to 36%, while Club and Cleo declined to 2% and 3%. Period 3 saw Aqua at 49%, Le Minerale at 33%, and Club/Cleo at 2% and 1%. In period 4, Aqua led with 45%, Le Minerale at 31%, and Club/Cleo/others at 2%, 1%, and 7%. Finally, in period 5, Aqua remained at 41%, Le Minerale fell to 28%, while others decreased to 6%, and Club/Cleo remained at 2% and 1%.